PENGARUH KEPEMIMPINAN TERHADAP KINERJA PEGAWAI DI PT BANK MANDIRI (PERSERO) TBK. CABANG KERINCI KABUPATEN PELALAWAN - Herman, Herman (Sekolah Tinggi Ilmu Ekonomi Riau, 2021)
This research was conducted at PT. Bank Mandiri (Persero) Tbk. Kerinci Branch, Pelalawan Regency. The purpose of this study was to determine whether leadership has a significant effect on employee performance at PT Bank Mandiri (Persero) Tbk. Kerinci Branch, Pelalawan Regency. The population in this study amounted to 36 people. In this study, the sample was taken using a saturated sample, which was 35 people. The data used are primary and secondary data with analysis using simple linear regression.The results showed that leadership has a positive direction on employee performance,it can be seen in the simple linear regression equation, namely Y=13,120+0,562X. And leadership has a significant effect on employee performance, namely the value of t_count > t_table (5,062>2,03452) or the value of Sig.<0.05.The magnitude of the influence of leadership on employee performance is 43.7 percent while the remaining 56.3 percent describes other independent variables not observed in this study